2018
DOI: 10.1039/c7ra08191j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological performance of a hybrid MMC coating deposited on Al–17Si piston alloy by laser composite surfacing technique

Abstract: Laser composite surfacing (LCS) is a photon driven manufacturing technology that can be utilized for depositing hybrid metal matrix composite coatings (HMMC) on softer Ti/Al/Mg alloys to enhance their tribo-mechanical properties. LCS offers the advantages of higher directionality, localized microstructural refinement and higher metallurgical bonding between coating and substrate. The current research presents the tribo-mechanical evaluation and characterization of solid lubricant based Ni-WC coatings deposited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Aluminum and titanium have been explored as an alternative to heavy-duty steel to produce machine parts [ 187 , 188 ]. Reinforcement of metals and alloys along with solid lubricants, hard ceramic particles, and fibers have been an area of interest in the development of MMC with precise balances of mechanical, physical and tribological characteristics [ 189 , 190 ]. Metal matrix composites reinforced with carbon, polymer, or ceramic fibers with varying compositions of solid-lubricant content have been investigated extensively for spacecraft applications [ 21 ].…”
Section: Metals Ceramic and Polymer-based Matrix Compositesmentioning
confidence: 99%
See 1 more Smart Citation
“…Aluminum and titanium have been explored as an alternative to heavy-duty steel to produce machine parts [ 187 , 188 ]. Reinforcement of metals and alloys along with solid lubricants, hard ceramic particles, and fibers have been an area of interest in the development of MMC with precise balances of mechanical, physical and tribological characteristics [ 189 , 190 ]. Metal matrix composites reinforced with carbon, polymer, or ceramic fibers with varying compositions of solid-lubricant content have been investigated extensively for spacecraft applications [ 21 ].…”
Section: Metals Ceramic and Polymer-based Matrix Compositesmentioning
confidence: 99%
“…MoS 2 , as the most successful solid lubricant in space applications, has gained a lot of eminence in the field of solid-lubrication research. Additionally, some investigations reported the use of Ni, WC, c-BN, and graphite solid-lubrication coatings on softer materials such as aluminum alloys to increase the surface hardness [ 190 , 191 , 192 ]. By contrast, the focus of automobile industries has primarily been on mixed lubrication, which is the combination of solid and liquid lubricants to address their tribological focused challenges.…”
Section: Metals Ceramic and Polymer-based Matrix Compositesmentioning
confidence: 99%
“…In this way, the durability of the RAM coatings can be checked and improved. We have tested these coatings in the X band (8)(9)(10)(11)(12). Further testing can be done in the Ku band (12)(13)(14)(15)(16)(17)(18) to improve the results further and to check the effectiveness of these coatings in higher bands.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The thickness of the RAM coating is proportional to the complex permittivity and permeability, and it can be varied correspondingly to the absorption band we want to overcome [9]. Structural material production is an emerging field, and day by day, many materials are formed by using composites knowledge [10,11,12]. These materials have several properties, and many composites are formed to be utilized in the aerospace industry.…”
Section: Introductionmentioning
confidence: 99%
“…Since the surface of such substrates inevitably experiences all kinds of friction in practical applications, so much attention has been paid to promote the wear resistance of superhydrophobic exible materials in recent years. [41][42][43][44][45][46][47][48][49] One approach to create a durability of superhydrophobic surfaces is to endow materials with the ability to regenerate the surface roughness or restore the hydrophobic components. Zhang et al 50 reported a long lasting superhydrophobic surfaces by spraying polystyrene/SiO 2 core/shell particles as a coating skeleton and polydimethylsiloxane (PDMS) as hydrophobic interconnection.…”
Section: Introductionmentioning
confidence: 99%